Optimal Line Balancing with Region Approach and Ranked Positional Weight: Penyeimbangan Garis Optimal dengan Pendekatan Wilayah dan Bobot Posisi Berurutan - Zahra, Salsabila Aulia; Rusindiyanto, Rusindiyanto (Indonesian Journal of Innovation Studies, 2025)
General Background: Micro, small, and medium enterprises (MSMEs) are vital to regional economic growth, yet many face production inefficiencies. Specific Background: UMKM Aneka Songkok Jombang, a producer of embroidered songkok, struggles with unbalanced production lines causing excessive work-in-progress, long waiting times, and unmet market demand. Knowledge Gap: Previous studies seldom compare line-balancing methods tailored to small-scale handicraft industries with complex station workflows. Aims: This research aims to enhance production line performance by applying the Region Approach (RA) and Ranked Positional Weight (RPW) methods to achieve optimal line balancing. Results: Stopwatch Time Study revealed initial efficiency of 47%, balance delay of 53%, and idle time of 45.24 minutes. Implementation of RA improved efficiency to 74%, reduced balance delay to 26%, and cut idle time to 14.41 minutes, while RPW achieved superior outcomes with 82% efficiency, 18% balance delay, and 8.87 minutes idle time. Novelty: This study provides a comparative evaluation of RA and RPW in a traditional MSME context, highlighting RPW’s higher effectiveness for small-scale, high-variability production. Implications: Findings guide MSMEs in adopting RPW for strategic line balancing, enabling improved productivity, reduced waste, and enhanced competitiveness in local and international markets. Highlights: RPW method achieved the highest efficiency (82%) with the lowest idle time (8.87 minutes). Comparative analysis shows RPW outperforms RA for small-scale production balancing. Implementation reduces work-in-progress and meets increasing market demand. Keywords: Line Balancing, Region Approach, Ranked Positional Weight, Songkok Production, MSME Efficiency